Body size is a sensitive trait-based indicator of soil nematode community response to fertilization in rice and wheat agroecosystems. (September 2015) - Liu, Ting; Guo, Rui; Ran, Wei; Whalen, Joann K.; Li, Huixin
Abstract: Nematode body size is a trait that could be responsive to environmental changes, such as agricultural management practices, and adopted as a standard trait-based indicator in soil community analysis. Our study investigated how body size in the nematode community responded to fertilization in a double-cropping system with paddy rice and upland wheat. Four fertilizer treatments were examined: an unfertilized control (CK), chemical fertilizer (CF), manure plus chemical fertilizer (MCF) and manure plus straw plus chemical fertilizer (MSCF). The community-weighted mean (CWM) of body size was the trait-based indicator used for nematode community analysis. A trend of increasing body size in fertilized plots was observed for most genera, with a relatively small increase in the size of small-bodied bacterivores and fungivores and a relatively large increase in the size of large-bodied omnivores. Fertilized plots had significantly greater CWM of body size than the CK treatment, although total nematode abundance increased significantly in the MSCF treatment only. Discriminant and multiple regression analyses showed that CWM of body size was positively correlated with the soil organic C, total N, available P and available K concentrations, which responded to fertilizer inputs. In contrast, soil fertility was weakly related to total body size in the wheat phase and the following abundance-based indicators: Margalef's richness index, Shannon's diversity index, summed maturity index (∑MI) and enrichment index (EI) in both phases. Since fertilization resulted in larger body size but no other change in the nematode community (i.e. diversity and abundance were generally unaffected by fertilization), this implies that nematodes have a plastic growth habit that does not necessarily result in greater reproduction or fitness of offspring. We suggest that CWM of body size is a reliable trait-based indicator of the soil nematode community response to fertilization, but this requires further testing across a wider range of fertilized agroecosystems. Highlights: Compared trait- and abundance-based indicators of soil nematode communities. Body size of most nematode genera was increased by fertilization. Community-weighted mean of body size correlated positively with soil nutrients. Abundance-based indicators weakly related to soil nutrients.